Evaluasi Tingkat Kematangan Sistem Informasi Rumah Sakit Menggunakan Information Technology Infrastructure Library Versi 3 : Studi Kasus : Rumah Sakit Amanah Sumpiuh - Aniec Anafisah Pratiwi; Adhim Tanfitra; Umar Abdul Abid; Ito Setiawan (Merkurius : Jurnal Riset Sistem Informasi dan Teknik Informatika, 2024)
Hospital Information System (HIS) is an important component in supporting effective and efficient health services. Evaluation of the maturity of information systems is needed to ensure that the implementation of SIRS is in accordance with the standards and needs of the organization. This study aims to evaluate the maturity level of information systems at Amanah Hospital using the Information Technology Infrastructure Library (ITIL) version 3 framework, specifically in the Service Operation domain. The research method uses a quantitative approach with data collection through questionnaires distributed to respondents involved in managing information systems. The evaluation was carried out on five subdomains, namely Event Management, Incident Management, Request Fulfillment, Problem Management, and Access Management. The results showed that the maturity level of the Amanah Hospital information system was at level 3.81 (Managed), with the highest value in the Incident Management and Access Management subdomains (4.00), while the lowest value in Event Management and Request Fulfillment (3.66). Based on these results, several improvements are recommended including the development of an integrated monitoring system, strengthening operational procedures, improving HR competencies, and implementing more structured periodic evaluations to achieve an optimal level of maturity.